162k views
21 votes
If f(x) = 3x − 1 and g(x) = x + 2, find (ƒ– g)(x) ​

User Martim
by
5.0k points

1 Answer

0 votes


\quad \huge \quad \quad \boxed{ \tt \:Answer }


\qquad \tt \rightarrow \:2x - 3

____________________________________


\large \tt Solution \: :


\qquad \tt \rightarrow \: (f - g)(x)


\qquad \tt \rightarrow \: f(x) - g(x)

Simple procedure :


\qquad \tt \rightarrow \: 3x - 1 - (x + 2)


\qquad \tt \rightarrow \: 3x - 1 - x - 2


\qquad \tt \rightarrow \: 3x - x - 1 - 2


\qquad \tt \rightarrow \: 2x - 3

Answered by : ❝ AǫᴜᴀWɪᴢ ❞

User Badcompany
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.